ANALISIS KETERAMPILAN BERPIKIR TINGKAT TINGGI DALAM MENYELESAIKAN SOAL UN FISIKA SMA PADA MATERI MEDAN MAGNET SISWA KELAS XII DI SMA MUHAMMADIYAH 3 JEMBER - Qurrotu A'yunina (LP3M IAI Al-Qolam, 2019)
This study aims to describe the high-level thinking skills of students in solving high school physics UN questions on magnetic field material. This research is a type of descriptive research with research subjects namely students of class XII MIPA Muhammadiyah 3 Jember High School. The data collection technique used was a written test consisting of five UN questions of magnetic field material that was modified in the form of descriptive questions. Based on the results of the study, the average percentage of high-level thinking skills of students in completing the National Examination (UN) questions on high school physics in magnetic field material is as follows: the analysis stage is 33.13%, the evaluation stage is 29.77%, and the creative stage is 21.05%. The analysis phase has a large percentage so that it shows students are able to decipher information (known and asked) as well as steps to solve the problems given. While the creation stage has a low percentage so that it shows students are not accustomed to re-checking answers according to known data with coherent steps.